Constructing Curricula: Rational choices around the use of simulations for optimal outcomes for students - Margaret McMillan; Mee Young Park; Susie Yoon (Halla Newcastle Education and Research Center, 2018)
Purpose To highlight the value of using guidelines for determining the worth of learning events that center on simulations health profession practice. Methods Literature Review, Identification of principles to guide key faculty members around decision-making for optimal educational practices in the use of simulations. Results Collaborative practices in formative and summative curriculum evaluations involving academics lead to a better appreciation of the need for rational decisions at both the macro level (Course Design) and micro-level (implementation phase) of curriculum development. Conclusion Actual and simulated health professional practice provide numerous examples of situations that could be chosen to drive student learning. The selection of meaningful practice situations across the entire program needs to be based on agreed upon principles and criteria for selection. The latter need to reflect the conceptual framework of the curriculum.